1910
DOI: 10.1103/physrevseriesi.31.159
|View full text |Cite
|
Sign up to set email alerts
|

The Calibration of Copper-Constantan Thermoelements

Abstract: HE practical usefulness of a thermoelement will often depend •*• on whether its readings can readily be interpreted in terms of the standard scale of temperature, that is, on the ease and accuracy with which it can be calibrated. The present work was undertaken for two reasons, first, to obtain a calibration curve for a particular pair of elements which had been in use at the Geophysical Laboratory, and second, to obtain data relating to the calibration of copper-constantan thermoelements in general. The two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1937
1937
1947
1947

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…A 50-j unction copper-constantan thermocouple was constructed and calibrated following all the precautions suggested by White (16)(17)(18)(19). The calibration of the thermocouple gave the following equation relating temperature to potential: = 0.5149S -2.501 X 10-4E2 G, water level; if, ice and water mixture; 7, electrical leads to heater coil where E is expressed in millivolts, and in 0 C. The reference point was the ice point.…”
Section: Apparatusmentioning
confidence: 99%
“…A 50-j unction copper-constantan thermocouple was constructed and calibrated following all the precautions suggested by White (16)(17)(18)(19). The calibration of the thermocouple gave the following equation relating temperature to potential: = 0.5149S -2.501 X 10-4E2 G, water level; if, ice and water mixture; 7, electrical leads to heater coil where E is expressed in millivolts, and in 0 C. The reference point was the ice point.…”
Section: Apparatusmentioning
confidence: 99%
“…Whether or not a thermocouple will give the same e. m. f. reading for a given temperature after having been heated to some higher temperature level is important if accurate results are desired. White (9,11) showed that the vital part of a thermocouple is that along which there is a temperature gradient, since it is that part which mainly determines the calibration and constancy. If the thermocouple is always immersed to the same extent in the hot medium, and if the temperature distribution in the temperature gradient from the hot medium to the cooler medium is always the same, there is no change in the electromotive force-temperature relationship with heating and use even if the wires are not homogeneous over this section.…”
Section: Agreement Of Thermocouplesmentioning
confidence: 99%
“…In work of this nature the question naturally arises as to whether or not it is necessary to calibrate each individual thermocouple when the wires come from the same spools, how much deviation there is in the same type of thermocouple made of wires from different lots, and what effect heating the thermocouples to different temperature levels has on their electromotive force-temperature relationship. Although various investigators mention factors which tend to affect the electromotive force-temperature relationship of different types of thermocouples (1,3,(5)(6)(7)(9)(10)(11)(12), actual experimental data are very limited. Roeser and co-workers state that the guarantee limits on chromel-alumel thermocouples have been fixed by the manufacturers at ±2.8°C.…”
mentioning
confidence: 99%